2015
DOI: 10.1166/jcsmd.2015.1073
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of multimodal distributions for hybrid moment-based chemical kinetics

Abstract: The stochastic dynamics of biochemical reaction networks can be accurately described by discrete-state Markov processes where each chemical reaction corresponds to a state transition of the process. Due to the largeness problem of the state space, analysis techniques based on an exploration of the state space are often not feasible and the integration of the moments of the underlying probability distribution has become a very popular alternative. In this paper the focus is on a comparison of reconstructed dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The results revealed that the implications of a partially finite state space had not been completely understood in earlier studies and that the number of classical moment equations that are really needed is smaller than what was previously claimed. 11,12,35 The results of this paper can also be seen as the basis for a hybrid approach for the analysis of stochastic models of biochemical reaction networks. The binary variable representation of the network, and the derivation of moment equations from it, automatically keeps the full probability distribution over the finite part of the state space while resorting to low-order moments over the infinite part.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The results revealed that the implications of a partially finite state space had not been completely understood in earlier studies and that the number of classical moment equations that are really needed is smaller than what was previously claimed. 11,12,35 The results of this paper can also be seen as the basis for a hybrid approach for the analysis of stochastic models of biochemical reaction networks. The binary variable representation of the network, and the derivation of moment equations from it, automatically keeps the full probability distribution over the finite part of the state space while resorting to low-order moments over the infinite part.…”
Section: Discussionmentioning
confidence: 93%
“…Together with the fact that the classical moments can be recovered from the conditional moments, one reaches the mathematically quite unintuitive conclusion that more properties of the underlying probability distribution can be captured with a smaller number of equations. 11,12 In this paper, I will show that this result is only obtained because the N M, L classical moment equations contain many equations that are redundant. Specifically, while Eq.…”
Section: The Number Of Classical and Conditional Moment Equationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Historically related to the discrete models of Stuart Kauffman [11] and René Thomas [12], process hitting attempts to address problems of scalability in classical modeling methods while maintaining the highest degree of expressiveness possible. Formally a subclass of asynchronous automata, it relies on large degrees of abstraction to describe the system as a whole.…”
Section: Author Contributionsmentioning
confidence: 99%
“…In the most general sense, modeling approaches can be thought of as being either quantitative or qualitative. Quantitative methods, such as ordinary differential equations or the chemical master equation, are widespread in the literature [1][2][3][4][5][6][7][8][9][10][11]; when the model is well developed, the detail therein can be incredibly informative. However, these methods are not well suited for all applications.…”
Section: Introductionmentioning
confidence: 99%